Bioinspired Self‐Propulsion of Water Droplets at the Convergence of Janus‐Textured Heated Substrates. (26th July 2019) - Zhang, Peipei; Peng, Baoxu; Wang, Jingming; Jiang, Lei
Abstract: Controlled propulsion of liquid droplets on a solid surface offers viable applications in fog harvesting, heat transfer, microfluidics, and microdevice technologies. A prerequisite for the propulsion of liquid droplets is to break the wetting symmetry of a droplet and contact‐line pinning on the surface by harnessing surface energy gradient. Here, a series of Janus‐textured substrates is constructed to investigate the self‐propulsion of Leidenfrost droplets. It is found that the self‐propulsion of droplets occurs only on two special Janus‐textured substrates. Those are nanostructured silicon substrate bounded by smooth silicon substrate and the nanowire‐decorated microstructured silicon substrate bounded by micropillars with smooth surfaces. The difference in roughness between the two sides of the Janus‐textured substrates creates various numbers and sizes of vapor bubbles. The vapor bubbles cause the droplets to become turbulent, and a pressure gradient is generated. The sufficiently large pressure gradient propels the Leidenfrost droplet to move directionally. The propulsion direction is always toward areas with low roughness. Abstract : Self‐propulsion of Leidenfrost droplets can be controlled by the asymmetric structures of the Janus‐textured substrates. At low temperatures, the droplets asymmetrically spread toward areas with high roughness. At high temperatures, the self‐propulsion occurs only on Janus‐textured substrates with sufficiently large difference in roughness. The self‐propulsion direction shifts toward the regions with low roughness.